GAMBARAN SENYAWA FITOKIMIA PADA EKSTRAK DAUN KERSEN (Muntingia calabura L.) TERHADAP KEMATIAN LARVA NYAMUK Aedes aegyptii SECARA KUALITATIF - Rosintan Enggar Wahyuningdiah; Hajrah Hidriya; Hafiz Al Farizi (UPPM Politeknik Unggulan Kalimantan, 2025)
Dengue hemorrhagic fever is an annual epidemic disease in Indonesia caused by the Dengue virus carried by the Aedes aegyptii. Prevention of these diseases can be done by utilizing plants as natural insecticides, one of which is the kersen plant (Muntingia calabura L.). This study aims to determine the phytochemical content in kersen leaf extract (Muntingia calabura L.) and the effect of the extract as a natural insecticide on the larvae of Aedes aegyptii. This research process includes taking kersen leaves, making extracts, phytochemical tests and testing the effect of kersen leaf extract on Aedes aegyptii larvae. The results of phytochemical tests show that kersen leaf extract contains flavonoids, alkaloids, tannins, and saponins. Larval death tests prove that this compound is effective in killing Aedes aegyptii larvae, kersen leaf extract containing phytochemical compounds can potentially be a natural insecticide, the mechanism of action of these compounds can be in the form of inhibiting the course of breathing, disrupting the nervous system, and functioning as a stomach and digestive poison for Aedes aegyptii larvae. This causing the larvae of Aedes aegyptii to die so that they can control the population of Aedes aegyptii, so that it can help in the prevention of dengue hemorrhagic fever.